Preferensi dan Rasionalisasi Pilihan Politik Perempuan Minang Perkotaan di Kota Padang terhadap Perilaku Memilih dalam Pemilihan Umum - Yoserizal, Yoserizal; Asrinaldi, Asrinaldi (Jurnal Demokrasi, 2009)
This study was intended to describe the political preference and rationalization of Minang urban women and their political response. This study was conducted in two kelurahan (villages) representing the characteristics of central urban and suburban in the city of Padang. Quantitative approach with survey method was used in this study. Respondents in this study were chosen through stratified random sampling. The finding of this study indicated that the political preference of Minang urban women tended to be asimetrical, while their political rationalization did not run perfectly. Their restricted political preferences were influenced by their restricted in the process of political socialization since their childhood. Â  Kata kunci: Preferensi politik, rasionalisasi politik, perilaku memilih, pemilihan umum, perempuan Minang